Respect for males amid suppression of females: Selective use of aggression and fitness correlates in the male-dominated society of hamadryas baboons. Issue 165 (April 2022) - Evans, Katarina D.; Swedell, Larissa; Chowdhury, Shahrina
Abstract: Hamadryas baboons ( Papio hamadryas ) are a useful model for human social evolution for multiple reasons, including their multilevel society, intense cross-sex bonds, and intermale tolerance. Their most stable social grouping, the one-male unit (OMU)—comprising a leader male, females, and sometimes follower males—is formed via successive takeovers of individual females by males. While takeovers occur via both aggressive and non-aggressive mechanisms, aggressive herding is common during and after takeovers and appears crucial in maintaining OMUs. Here we use behavioral and demographic data from Filoha, Ethiopia to examine the relationship between aggressive takeovers and fitness correlates. We found no relationship between a male's percentage of takeovers that were aggressive and his presumed number of infants sired, nor his number of females or followers. However, we did find that a leader male's average intensity of aggression toward both other males and females around the time of a takeover was negatively related to his presumed number of infants sired. In addition, a leader male's average intensity of aggression toward other males was negatively related to his maximum number of followers. Finally, leader males exhibited more intense aggression toward females in interband, compared to intraband, takeovers. Our findings suggest that (1) leader males who limit their aggression toward other males may have greater success in attracting followers, thereby increasing their fitness via enhanced defense of the OMU; (2) exceptionally aggressive takeovers may lead to lower birth rates via female reproductive suppression; and (3) the extent to which males use aggression toward females depends on the context in which the takeover occurs. Overall, these results both suggest that hamadryas males use aggression selectively and underscore the ubiquity of intermale tolerance and female suppression in the hamadryas social system. This study lends insight into the interplay between male–female and male–male social dynamics during human evolution.